Effect of Ferrous and Vitamin E on Rabbit Serum Lipoproteins - Gholamreza Dashti; Masoud Poormoghadas; Mohammad Hosein Sanei; Mohsen Hoseini; Seyed Mohammad Ghayoomi (مجله دانشکده پزشکی اصفهان, 2011)
Background: Fatty streaks are the primary lesions to form atherosclerosis. Lipid per oxidation by free- radicals, plays an important role in plaque formation. Vitamin E, as a lipid in soluble vitamin, is an important antioxidant and may prevent or delay the coronary heart disease by limiting LDL oxidation. Our goal was to evaluate the effect of vitamin E and iron on blood serum lipids in male rabbits fed high-cholestrol diet. Method: Thirty white male rabbits were weighed and blood serum samples were taken for analysis of serum lipoproteins. They were randomly divided in to 5 groups each Containing 6 rabbits for 42 days. Group1 was given normal diet. Group 2 fed with high cholesterol (2 %) diet. Group 3 fed with high cholesterol diet with iron (50 mg/kg). Group 4 fed with high cholesterol diet with vitamin E (50 mg/kg). Group 5 fed with high cholesterol diet with iron (50 mg/kg) and vitamin E (50 mg/kg). These groups were again weighed and blood samples were taken for analysis of serum lipoproteins after 42 days. Results: Significant difference in cholesterol, LDL, HDL, TG, and VLDL were seen before and after the experiment in all 5 groups (P < 0.001). Conclusion: The significant difference was observed between all groups in relation to the effect of iron and vitamin E on lipid metabolism. While vitamin E has a protective role in atherosclerosis, it seems that iron has a provocation role in serum lipids.